2020
DOI: 10.1109/access.2020.3007536
|View full text |Cite
|
Sign up to set email alerts
|

Security and Performance in IoT: A Balancing Act

Abstract: With predictions suggesting there will be 18 billion Internet of Things (IoT) devices live by 2022, performance of these low powered devices, as well as security is of utmost importance. Managing security and performance is a balancing act. Achieving this balance will always continue to be a challenge. This research presents two main contributions to this area. The first contribution is a framework to measure cryptographic performance of IoT devices. The areas of measurement are power consumption, time cost, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In our previous research, the speed and efficiency of ChaCha20 has been demonstrated to exceed the performance of AES on multiple resource-constrained devices [35]. Previously, we created an authentication protocol based on ChaCha20-Poly1305 [36].…”
Section: Chacha20-poly1305 Aeadmentioning
confidence: 99%
“…In our previous research, the speed and efficiency of ChaCha20 has been demonstrated to exceed the performance of AES on multiple resource-constrained devices [35]. Previously, we created an authentication protocol based on ChaCha20-Poly1305 [36].…”
Section: Chacha20-poly1305 Aeadmentioning
confidence: 99%
“…Compared with JTAG download interface, they occupy less I/O interface of the single chip computer and do not need to carry other circuits during their use. Welding circuit can be directly connected, more convenient operation [4].…”
Section: Main Control Module Designmentioning
confidence: 99%
“…e advanced encryption standard (AES) and error-correcting codes (ECC) are mainly used as basic lightweight encryption elements. Various studies have been aimed to optimize lightweight encryption while balancing security and performance management [69][70][71][72][73][74][75][76].…”
Section: Keyword Clustering and Evolution Of Research On Iotmentioning
confidence: 99%